A Thermally Insulating Textile Inspired by Polar Bear Hair. Issue 14 (14th February 2018) - Cui, Ying; Gong, Huaxin; Wang, Yujie; Li, Dewen; Bai, Hao
Abstract: Animals living in the extremely cold environment, such as polar bears, have shown amazing capability to keep warm, benefiting from their hollow hairs. Mimicking such a strategy in synthetic fibers would stimulate smart textiles for efficient personal thermal management, which plays an important role in preventing heat loss and improving efficiency in house warming energy consumption. Here, a "freeze‐spinning" technique is used to realize continuous and large‐scale fabrication of fibers with aligned porous structure, mimicking polar bear hairs, which is difficult to achieve by other methods. A textile woven with such biomimetic fibers shows an excellent thermal insulation property as well as good breathability and wearability. In addition to passively insulating heat loss, the textile can also function as a wearable heater, when doped with electroheating materials such as carbon nanotubes, to induce fast thermal response and uniform electroheating while maintaining its soft and porous nature for comfortable wearing. Abstract : A textile with excellent thermal insulation capability, mimicking the porous structure of polar bear hair, is fabricated by a "freeze‐spinning" technique to continuously spin silk fibroin solution into aligned porous fibers. Doped with electroheating materials, this type of textile is beneficial for personal thermal management, thermal stealth in military applications, and wearable electronics.